Judicialização da educação infantil no estado de Goiás no período 2009-2019: análises e desafios - Machado, Elka Cândida de Oliveira (2021)
This study is part of the theme of judicialization of education. Its main objective is to analyze the way and measure of action of the Judiciary in the State of Goiás in relation to the right to early childhood education. Associated with this observation, the objective is to examine the national context of the right to early childhood education, as well as the trajectory of this educational stage and the norms for the construction of public policies; understand the phenomenon of judicialization of public policies, recognizing its limits and possibilities; inventory and analyze local data on the supply of vacancies and the jurisprudence of the Court of Justice of Goiás (TJGO) regarding early childhood education when required to render decisions in this domain. Qualitative research, of an empirical nature, is bibliographic and documentary, built on the basis of an understanding of: the right to education and the theory of fundamental rights (BARCELLOS, 2011; BOBBIO, 2004; CURY, 1998; DIMOULIS; MARTINS, 2014; SARLET, 2012); the trajectory of early childhood education (BARBOSA, 2008; KUHLMANN JR., 2015; OLIVEIRA, Z., 2011; VALDEZ, 2002); the judicialization of politics (BARROSO, 2003; HIRSCHL, 2009; SANTOS, 2011; TATE; VALLINDER, 1995; TAYLOR, 2007); judicial control of public policies (BARCELLOS, 2008; BARREIRO; FURTADO, 2015; COSTA, S., 2016; RODRÍGUEZ GARAVITO, 2017; VALLE, 2016); the judicialization of education (GOTTI, 2017; RANIERI, 2017; XIMENES; SILVEIRA, 2017; SILVEIRA, A., 2010, 2013) and the judicialization of early childhood education (CÔRREA, 2014; XIMENES; OLIVEIRA; SILVA, 2017). On the website of the Court of Justice of Goiás, judgments were raised that discussed the offer of vacancies individually and collectively between the years 2009 and 2019. characterization and mapping by year, region, author, arguments of municipalities and content of decisions. Identified the trend of judgments for the inclusion of children in day care centers and preschools, the analysis of the participation of the Judiciary Power of Goiás, through collective actions, in the public policy of the provision of early childhood education in the municipalities of: Goianira, Silvânia, Catalão, Rio Verde, Valparaíso, Pires do Rio and Aparecida de Goiânia. This research evidences the TJGO's favorable position on the right to early childhood education both from the perspective of individual and collective access between 2009 and 2019, following the decision handed down by the STF in 2005, through the Extraordinary Appeal - RE-AgR nº 410.715- 5/SP. Due to the time taken to process collective cases, sometimes the judicialization was not able to promote the care of children who were at the time on waiting lists, despite the expansion in the number of vacancies during the period of judicial discussion. About the materialization of the law, it demonstrates that although there is progress in the implementation of public policies, judicialization can be seen as a last but not definitive instrument in solving problems, since public policies are composed of complex variables and not linear. In the state of Goiás, the judicialization of early childhood education showed new designs and challenges to public policies. It was found that, in some cases, judicial decisions corroborated the distance between the stages (nursery and preschool). In addition, the judicial action revealed that, in the impossibility of offering vacancies by the state power, there is the possibility of allocating the fund to private institutions, erecting, at this point, an interpenetration between the public and the private with variants of appropriation of the fund. public by the private due to the absence of educational provision by the State.